Preparation of Microporous Carbon from Sargassum horneri by Hydrothermal Carbonization and KOH Activation for CO2 Capture. (13th December 2018) - Zeng, Ganning; Lou, Sa; Ying, Huijuan; Wu, Xi; Dou, Xin; Ai, Ning; Wang, Jiawei
Abstract : High-performance microporous activated carbon (AHC) for CO2 capture was prepared from an emerging marine pollutant, Sargassum horneri, via hydrothermal carbonization (HTC) and KOH activation. The as-synthesized carbon material was characterized by N2 sorption-desorption measurement, TGA, SEM, XRD, FTIR, and elemental analysis. Impressively, the activated carbon exhibited high specific surface area (1221 m 2 /g), narrow distributed micropores (∼0.50 nm), and a relatively high nitrogen content (3.56 wt.%), which endowed this carbon material high CO2 uptake of 101.7 mg/g at 30°C and 1 bar. Moreover, the carbon material showed highly stable CO2 adsorption capacity and easy regeneration over four adsorption-desorption cycles. Two kinetic models were employed in this work and found that the pseudo-first-order kinetic model ( R 2 = 0.99) provided the best description. In addition, the high CO2 uptake is mainly attributed to the presence of abundant narrow microporous. The macroporous structure of hydrochar (HC) played an important role in the production of microporous carbon with high adsorption properties. This work provides an efficient strategy for preparing microporous activated carbon from Sargassum horneri, and AHC is a promising candidate acting as an efficient CO2 adsorbent for further industrial application.